BIOGRAFI BURHANUDIN MAHIR (1954-2016) - Yogi Pratama, Abd Rahman (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract The puspose of the research to provide an overview of Burhanudin Mahir's Political Biography of 1954-2016. Starting from What is the background of education and socio-culture that affect the life of Burhanudin Mahir, to how the beginning of political career and the role of Burhanudin Mahir in building the area he leads. The method used in this research is a historical research method that systematically consists of four steps: heuristic, Criticism, Interpretation, Historiography.Research results obtained that Burhanudin Mahir was born in Jambi Kecil on 16 June 1954. He is the second of six brothers of the pair of Mahir Isaac and Arba'ah. He was raised in a religious, affluent and disciplined family because at that time his father was a Pasirah in Jambi Kecil village, Burhanudin Mahir could finish his education up to a bachelor degree at that time it was still very rare to find anyone who could get educational bench. He has held various important positions, starting from the position of chairman of the party, to the Chairman of the Batanghari District Legislative Council where he was the initiator of the Muaro Jambi regency, and his greatest momentum became the Regent of Muaro Jambi for two periods during which served as regent has many changes that he did from the field of Infrastructure, Education, Health, and Economics. Keywords: Biography Burhanudin Mahir (1954-2016), Political Career